Analysis of the Influence of Instagram Social Media and Influencer Marketing on The Intention to Buy of The Lecade Brand - Nugrahani, Ananda Zhafira; Ikhram , M. Abdi Dzil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose – This study aims to examine the influence of Instagram social media and influencer marketing on purchase intention toward the Lecade brand.   Design/methodology/approach – This study employs an explanatory research design to analyze the relationships between Instagram social media, influencer marketing, and purchase intention. Data were collected from 91 active Instagram users aged at least 18 years who follow the Lecade Instagram account, using a non-probability sampling method. The data were analyzed using IBM SPSS Statistics 26.   Findings – The results indicate that both Instagram social media and influencer marketing have a positive and significant effect on purchase intention toward the Lecade brand. These findings suggest that social media engagement and influencer-driven promotion play an important role in shaping consumers’ buying intentions in digital marketing environments.   Originality/value – This study contributes to digital marketing literature by highlighting the combined role of Instagram-based marketing and influencer strategies in influencing purchase intention for local brands. The findings provide practical insights for businesses in optimizing social media platforms and influencer collaborations to strengthen consumer buying interest.